2019
DOI: 10.1038/s41467-019-12423-y
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state polymer electrolytes for high-performance lithium metal batteries

Abstract: Electrochemical cells based on alkali metal anodes are receiving intensive scientific interest as potentially transformative technology platforms for electrical energy storage. Chemical, morphological, mechanical and hydrodynamic instabilities at the metal anode produce uneven metal electrodeposition and poor anode reversibility, which, are among the many known challenges that limit progress. Here, we report that solid-state electrolytes based on crosslinked polymer networks can address all of these challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 38 publications
2
135
1
Order By: Relevance
“…Zhang et al demonstrated a facile approach by UV irradiation to prepare a flexible PEO-based crosslinked electrolyte (PTT) consisting of linear PEO, tetraglyme (TEGDME), and tetraethylene glycol dimethacrylate (TEGDMA) ( Figure 10) [97]. The SPE exhibits superior electrochemical properties with high ionic conductivity (2.7 × 10 −4 S•cm −1 at 24 • C), high transference number (0.56), wide electrochemical stability window that exceeds 5 V (Li + /Li), and low interfacial resistance; similar SPEs have also been reported [98,99]. In the work of Choudhury et al [98], the crosslinked polymer matrix comprised of PEGDMA and bis(2-methoxyethyl) ether (diglyme), and the T g and mechanical strength were found to increase with the PEGDMA content as shown in Figure 11.…”
Section: Crosslinked Polymermentioning
confidence: 54%
See 2 more Smart Citations
“…Zhang et al demonstrated a facile approach by UV irradiation to prepare a flexible PEO-based crosslinked electrolyte (PTT) consisting of linear PEO, tetraglyme (TEGDME), and tetraethylene glycol dimethacrylate (TEGDMA) ( Figure 10) [97]. The SPE exhibits superior electrochemical properties with high ionic conductivity (2.7 × 10 −4 S•cm −1 at 24 • C), high transference number (0.56), wide electrochemical stability window that exceeds 5 V (Li + /Li), and low interfacial resistance; similar SPEs have also been reported [98,99]. In the work of Choudhury et al [98], the crosslinked polymer matrix comprised of PEGDMA and bis(2-methoxyethyl) ether (diglyme), and the T g and mechanical strength were found to increase with the PEGDMA content as shown in Figure 11.…”
Section: Crosslinked Polymermentioning
confidence: 54%
“…The SPE exhibits superior electrochemical properties with high ionic conductivity (2.7 × 10 −4 S•cm −1 at 24 °C), high transference number (0.56), wide electrochemical stability window that exceeds 5 V (Li + /Li), and low interfacial resistance; similar SPEs have also been reported [98,99]. In the work of Choudhury et al [98], the crosslinked polymer matrix comprised of PEGDMA and bis(2-methoxyethyl) ether (diglyme), and the Tg and mechanical strength were found to increase with the PEGDMA content as shown in Figure 11. The authors observed that the materials behaved as single-phase soft solids at a critical PEGDMA content of 40%.…”
Section: Crosslinked Polymermentioning
confidence: 63%
See 1 more Smart Citation
“…SPEs are at horoughly explored topic in lithiumion battery research, as it pertainst ot he improvemento ft he energy density of the lithium-ion battery. [195][196][197] The application of SPE electrolyzers and PEM reactors can also be found in chemicalf uel cells, where the catalyst-loaded electrodes are fused onto both sides of the membrane to form am embrane electrode assembly (MEA). [198] In some examples, the catalytic metals are deposited directly on membrane surfaces.…”
Section: Solid Polymer Electrolyte Electrolyzerorp Em Reactormentioning
confidence: 99%
“…With the deepening research on all-solid-state batteries (ASSBs), an intensive scientific interest in the development of inherent safety, non-leakage, and stable high-performance electrochemical equipment has emerged to accommodate a wide range of new engineering applications, including medical implants, flexible electronics, and textiles [ 1 , 2 ]. In contrast to inorganic counterparts with a brittle crystalline phase, the solid polymer electrolyte (SPE) exhibits excellent interfacial compatibility, and superior elasticity to endure greater mechanical deformation, contributing to be cast into the complicated architectures for lithium-ion and lithium-metal batteries [ 3 , 4 , 5 ]. Consequently, a wide array of polymers such as poly (ethylene oxide) (PEO) [ 6 , 7 , 8 , 9 ], polyacrylonitrile (PAN) [ 10 , 11 , 12 , 13 ], poly (vinylidene fluoride) (PVdF) [ 14 , 15 ], and its copolymer with hexafluoropropylene (PVdF-HFP) [ 16 , 17 ], poly (methyl methacrylate) (PMMA) [ 18 , 19 , 20 ], and poly (vinyl alcohol) (PVA) [ 21 , 22 , 23 , 24 ], as well as their mixtures [ 25 , 26 , 27 , 28 ], have been adopted as the potential matrices for solid electrolytes.…”
Section: Introductionmentioning
confidence: 99%